Pengaruh Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Karyawan - Abdul Faqih (MANABIS: Jurnal Manajemen dan Bisnis, 2024)
This research examines the impact of work discipline and motivation on employee performance at PT. UPS Cardig International, where performance has declined. Using a quantitative descriptive approach, the study surveyed 96 respondents selected via simple random sampling from a total workforce of 138 across all divisions. Data collection involved an online Google Form survey, with analysis conducted using SmartPLS version 3.2.9. Results indicate that both work discipline and motivation positively and significantly influence employee performance. The findings suggest that implementing effective practices in these areas can improve employee performance at PT. UPS Cardig International. Based on these results, the study recommends that companies enhance employee development programs focusing on discipline and work motivation. However, limitations in variable complexity and data acquisition highlight the need for further research to gain a deeper understanding of factors affecting employee performance. This study contributes to the body of knowledge on employee performance management, offering insights for PT. UPS Cardig International and similar organizations facing performance challenges. By emphasizing the importance of work discipline and motivation, the research provides a foundation for developing targeted strategies to enhance employee productivity and overall organizational effectiveness.